Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

briangtt

  • 3 years ago

Solve the DE using method of undetermined coefficients y"'-6y"+11y'-6y=2xe^-x

  • This Question is Open
  1. mark_o.
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    hi you can start with finding you Yc y"'-6y"+11y'-6y=2xe^-x y"'-6y"+11y'-6y=0 m^3 -6m^2 +11m -6=0 m=1,2,3 therefore Yc=C1e^x +C2 e^2x +C3 e^3x now find Yp by using Yp=(Ax+B)e^-x Yp'=___? Yp''=____? Yp'''=_____? then sub them to the original equation

  2. mark_o.
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    @ briangtt

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy